Preparation method of low-Pt alloy catalyst
By adding ethylene glycol to the front -drive scattered solution and combined with glow discharge plasma treatment, the low PT alloy catalyst is prepared to solve the problem of low catalyst PT load capacity, and the high -efficiency preparation and performance improvement of the catalyst.
Patent Information
- Application Number
- CN202411469436.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the Pt loading of the catalyst prepared by glow discharge technology is relatively low, which limits the further improvement of catalytic activity.
By adding glycol to the front -drive scattered liquid, and combined with goblin discharge plasma treatment, the low PT alloy catalyst is prepared. This method includes the pre -processing of carbon -based vectors, the preparation of the PT front drive dispersal, the light discharge treatment, and the formation of the catalyst.
Effectively improve the PT load rate of catalysts, significantly promote the uniform distribution and catalytic effectiveness of catalysts, reduce the amount of precious metal PT, control production costs, and improve the catalytic activity and antisidification performance of catalysts.
Smart Images

Figure CN119361733A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fuel cells, and in particular to a method for preparing a low-Pt alloy catalyst. Background Art
[0002] With the continuous development of the global economy and the continuous growth of the population, the demand for energy has increased dramatically. The reserves of traditional fossil fuels such as oil, natural gas and coal are decreasing, and the environmental pollution caused by their combustion is becoming increasingly serious. Therefore, the development of clean, efficient and renewable new energy technologies has become a key direction for global scientific research and industrial development. Fuel cells, as an efficient and clean energy conversion device, directly convert the chemical energy in the fuel into electrical energy through an electrochemical process. It has the advantages of high energy conversion efficiency, green environmental protection, recyclability and fast startup, and is regarded as the primary energy technology leading global sustainable development.
[0003] However, the commercialization of fuel cells is severely restricted by high costs, of which the cost of catalysts accounts for a considerable proportion. In particular, Pt-based catalysts, as the most widely studied fuel cell catalysts, have excellent catalytic performance, but their high price, poor stability, catalytic activity and low Pt atom utilization efficiency limit their large-scale application. Therefore, the development of efficient, low-cost and highly stable ORR catalysts has become an important research direction in the field of fuel cells.
[0004] Traditional Pt-based catalyst preparation methods, such as impregnation-liquid phase reduction method, colloid method, gas phase reduction method, electrochemical deposition method, ion exchange method, etc., have improved the catalytic activity of the catalyst to a certain extent, but there are still problems such as complex operation process, difficult to control particle size, and low catalytic efficiency. Especially in the preparation process of the catalyst, how to effectively control the catalyst loading, particle size and dispersion to further improve its catalytic activity and stability, and control its preparation cost is a hot spot and difficulty in the current catalyst research field.
[0005] The technical solution of invention patent CN117039031A adopts a glow discharge method which is easy to operate, green and environmentally friendly, and can effectively control particle agglomeration. However, the loading rate of Pt atoms in the catalyst prepared by this method is low, which limits the further improvement of the catalytic activity. Summary of the invention
[0006] In view of the technical problem of low Pt loading in the catalyst prepared by glow discharge technology in the prior art, the present invention provides a method for preparing a low Pt alloy catalyst, comprising the following steps:
[0007] S1: pretreatment of the carbon-based carrier, adding the carbon-based carrier to an acid solution, dispersing the carbon-based carrier by ultrasonication, and then condensing and refluxing the carbon-based carrier, and washing, filtering, and drying the condensed and refluxed solution to obtain an activated carrier;
[0008] S2: Preparation of Pt precursor dispersion, dissolving Pt precursor, metal ion salt solution and the activated carrier in water to obtain a mixed solution, adding ethylene glycol to the mixed solution and adjusting the pH of the solution to alkaline, and finally performing ultrasonic treatment to obtain a Pt precursor dispersion;
[0009] S3: glow discharge plasma treatment, placing the Pt precursor dispersion in a reaction liquid container of a plasma generator, then turning on a DC power switch, adjusting the DC power voltage to perform glow discharge plasma treatment, and obtaining a discharge product;
[0010] S4: Formation of a Pt alloy catalyst. The discharge product is filtered and washed with a washing liquid, and then dried and ground to obtain a low-Pt alloy catalyst.
[0011] Furthermore, the carbon-based carrier is one of conductive carbon black, carbon nanotubes, graphene, Ketjen black, acetylene black, ethanol, glucose and sucrose.
[0012] Furthermore, the acid solution is one of citric acid, acetic acid, sulfuric acid, perchloric acid, nitric acid, and oxalic acid aqueous solutions, and the concentration of the acid solution is 0.1 to 2.0 mol / L.
[0013] Furthermore, in step S1, the temperature of the condensation reflux is 60° C. to 80° C., and the duration is 5 to 8 hours, and the washing method is to wash with deionized water for 3 to 6 times.
[0014] Furthermore, the Pt precursor includes at least one of chloroplatinic acid, potassium chloroplatinate, potassium chloroplatinite, sodium hexachloroplatinate hexahydrate, sodium chloroplatinite, and platinum nitrate.
[0015] Furthermore, the salt solution of metal ions is a salt solution of one or more metal ions of non-platinum noble metals and transition metals.
[0016] Furthermore, the volume ratio of the mixed liquid to the ethylene glycol is 1:1-3, the Pt concentration in the Pt precursor dispersion is 0.005-0.05 mol / L, and the molar ratio of Pt to the metal element is 1:1-10.
[0017] Furthermore, the ultrasonic treatment time in step S2 is 30 to 60 minutes.
[0018] Furthermore, the DC power supply voltage of the glow discharge plasma treatment is 400-600V.
[0019] Furthermore, the washing liquid is at least one of deionized water, ethanol and methanol.
[0020] The beneficial effects of the present invention are as follows:
[0021] 1. The present invention effectively solves the technical problem of low Pt loading in the preparation of catalysts by glow discharge plasma treatment by adding ethylene glycol to the precursor dispersion and optimizing its dosage. When the Pt dosage is much lower than that recorded in the comparative documents, the loading rate is effectively improved by more than 10%.
[0022] 2. In the technical solution of the present invention, ethylene glycol is used as a reducing agent to reduce the Pt ions in the Pt salt solution to metallic Pt. It is also used as a dispersing solvent to effectively prevent the agglomeration of Pt nanoparticles and ensure the uniform dispersion of Pt nanoparticles on the surface of the carbon-based carrier. In addition, the glow discharge treatment can increase the defects on the surface of the carrier, thereby expanding the specific surface area, providing more anchoring points for Pt nanoparticles, and enhancing the electronic coupling effect. The use of ethylene glycol in combination with the glow discharge treatment achieves the technical effect of "1+1>2", significantly promoting the uniform distribution of ionomers and the improvement of catalytic efficiency.
[0023] 3. Transition metal elements are introduced in the process of preparing the catalyst of the present invention, and the ratio of Pt to transition metal elements is as low as 1:10, which greatly reduces the amount of precious metal Pt, effectively controls the production cost, and also significantly improves the catalytic activity and anti-poisoning performance of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0025] Figure 1 This is the TEM (Mapping) image of the Pt-Ni-C alloy catalyst prepared in Example 1 of the present invention.
[0026] Figure 2 This is a LSV comparison chart of the Pt-Ni-C alloy catalyst prepared in Example 1 of the present invention and commercial Pt / C.
[0027] Figure 3 This is a LSV comparison chart of the Pt-Co-Ni-C alloy catalyst prepared in Example 2 of the present invention and commercial Pt / C. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] The present invention provides a method for preparing a low-Pt alloy catalyst, comprising the following steps:
[0030] S1: pretreatment of the carbon-based carrier, adding the carbon-based carrier to an acid solution, dispersing the carbon-based carrier by ultrasonication, and then condensing and refluxing the carbon-based carrier, and washing, filtering, and drying the condensed and refluxed solution to obtain an activated carrier;
[0031] S2: Preparation of Pt precursor dispersion, dissolving Pt precursor, metal ion salt solution and the activated carrier in water to obtain a mixed solution, adding ethylene glycol to the mixed solution and adjusting the pH of the solution to alkaline, and finally performing ultrasonic treatment to obtain a Pt precursor dispersion;
[0032] S3: glow discharge plasma treatment, placing the Pt precursor dispersion in a reaction liquid container of a plasma generator, then turning on a DC power switch, adjusting the DC power voltage to perform glow discharge plasma treatment, and obtaining a discharge product;
[0033] S4: Formation of a Pt alloy catalyst. The discharge product is filtered and washed with a washing liquid, and then dried and ground to obtain a low-Pt alloy catalyst.
[0034] This solution effectively solves the technical problem of low Pt loading when preparing catalysts using glow discharge plasma treatment by adding ethylene glycol to the precursor dispersion.
[0035] Ethylene glycol acts as a reducing agent to reduce Pt ions in the Pt salt solution to metallic Pt. It also acts as a dispersing solvent, effectively preventing the agglomeration of Pt nanoparticles and ensuring the uniform dispersion of Pt nanoparticles on the surface of the carbon-based carrier. In addition, glow discharge treatment can increase the defects on the carrier surface, thereby expanding the specific surface area, providing more anchoring points for Pt nanoparticles, and enhancing the electronic coupling effect. The combined use of ethylene glycol and glow discharge treatment achieves the technical effect of "1+1>2", significantly promoting the uniform distribution of ionomers and improving catalytic efficiency.
[0036] Furthermore, the carbon-based carrier is one of conductive carbon black, carbon nanotubes, graphene, Ketjen black, acetylene black, ethanol, glucose and sucrose.
[0037] Furthermore, the acid solution is one of citric acid, acetic acid, sulfuric acid, perchloric acid, nitric acid, and oxalic acid aqueous solutions, and the concentration of the acid solution is 0.1 to 2.0 mol / L.
[0038] Furthermore, in step S1, the temperature of the condensation reflux is 60° C. to 80° C., and the duration is 5 to 8 hours, and the washing method is to wash with deionized water for 3 to 6 times.
[0039] This scheme utilizes an acidic solution to circulate the acid on the carrier surface through condensation reflux, thereby removing impurities from the carbon-based carrier, increasing the surface roughness and specific surface area of the carrier, and optimizing the pore size and pore structure, promoting the uniform dispersion and stable attachment of Pt catalyst particles on the carrier, thereby improving the electrocatalytic activity and stability of the catalyst.
[0040] Furthermore, the Pt precursor includes at least one of chloroplatinic acid, potassium chloroplatinate, potassium chloroplatinite, sodium hexachloroplatinate hexahydrate, sodium chloroplatinite, and platinum nitrate.
[0041] Furthermore, the salt solution of metal ions is a salt solution of one or more metal ions of non-platinum noble metals and transition metals.
[0042] Furthermore, the volume ratio of the mixed liquid to the ethylene glycol is 1:1-3, the Pt concentration in the Pt precursor dispersion is 0.005-0.05 mol / L, and the molar ratio of Pt to the metal element is 1:1-10.
[0043] This scheme introduces transition metal elements, and the ratio of Pt to transition metal elements is as low as 1:10, which greatly reduces the amount of precious metal Pt, effectively controls the production cost, and significantly improves the catalytic activity and anti-poisoning performance of the catalyst. At the same time, when the amount of Pt is much lower than that recorded in the comparative documents, the loading rate has been effectively improved by more than 10%.
[0044] Furthermore, the ultrasonic treatment time in step S2 is 30 to 60 minutes.
[0045] Furthermore, the DC power supply voltage of the glow discharge plasma treatment is 400-600V.
[0046] Furthermore, the washing liquid is at least one of deionized water, ethanol and methanol.
[0047] In the preparation process of Pt catalyst, the Pt loading of the catalyst obtained by glow discharge plasma treatment alone is very low, and the simple ethylene glycol reduction treatment cannot effectively adjust the active sites of the support material. The combined use of the two is not a simple combination, but will introduce new technical problems and reaction effects, such as the adjustment of pH value, temperature and processing steps, which requires creative optimization of the preparation conditions and processes of low Pt alloy catalysts. The scheme provided by the present invention successfully achieves the effective preparation of low Pt alloy catalysts by optimizing the support material, the ratio of Pt to transition elements, the selection of pickling solvents, the types of washing liquids, and the process conditions such as ultrasonic treatment, plasma treatment and pickling, and significantly improves the Pt loading and catalytic efficiency of the catalyst.
[0048] Example 1
[0049] Preparation of Pt-Ni-C alloy catalyst:
[0050] S1: The carbon-based carrier is subjected to an acidification reflux treatment. 100 mL of concentrated nitric acid and 1 g of Ketjen black are stirred for 30 min, ultrasonicated for 30 min, condensed and refluxed at 60 ° C for 6 h, and then washed with deionized water for 3 times. After vacuum drying, the acidified carbon-based carrier is obtained;
[0051] S2: Synthesis of Pt precursor dispersion: 200 mg of the acidified carbon-based support was mixed with 3.12 g of chloroplatinic acid, 2.33 g of Ni(NO 3 ) 2 6H 2 O was mixed with deionized water to prepare a 100 mL solution, 100 mL of ethylene glycol was added, and then NaOH solution was added dropwise to adjust the pH to alkaline, and finally ultrasonic treatment was performed for 1 h, and the molar ratio of Pt salt to the second component Ni metal salt was 1:1;
[0052] S3: Glow discharge plasma treatment of the synthesized Pt precursor dispersion was performed at a voltage of 500 V for 30 min;
[0053] S4: The obtained discharge product was washed with deionized water for three times and filtered, and the obtained sample was placed in a 60° C. vacuum drying oven for drying, and finally taken out and ground into powder, i.e., Pt-Ni-C alloy catalyst.
[0054] Example 2
[0055] Preparation of Pt-Co-Ni-C Alloy Catalyst
[0056] S1: The carbon-based carrier is subjected to an acidification reflux treatment. 100 mL of concentrated nitric acid and 1 g of Ketjen black are stirred for 30 min, ultrasonicated for 30 min, condensed and refluxed at 60 ° C for 5 h, and then washed with deionized water for 3 times. After vacuum drying, the acidified carbon-based carrier is obtained;
[0057] S2: Synthesis of Pt precursor dispersion: 200 mg of the acidified carbon-based support was mixed with 3.12 g of chloroplatinic acid, 3.49 g of Ni(NO 3 ) 2 6H 2 O, 3.49 g Co(NO 3 ) 2 6H 2 O was mixed with deionized water to prepare a 100 mL solution, 100 mL of ethylene glycol was added, and then NaOH solution was added dropwise to adjust the pH to alkaline, and finally ultrasonic treatment was performed for 1 h, and the molar ratio of Pt salt to metal salt was 1:3;
[0058] S3: Glow discharge plasma treatment of the synthesized Pt precursor dispersion was performed at a voltage of 500 V for 30 min;
[0059] S4: The obtained discharge product was washed with deionized water for three times and filtered, and the obtained sample was placed in a 60° C. vacuum drying oven for drying, and finally taken out and ground into powder, i.e., Pt-Co-Ni-C alloy catalyst.
[0060] Example 3
[0061] Preparation of Pt-Co-C Alloy Catalyst
[0062] S1: The carbon-based carrier is subjected to an acidification reflux treatment. 100 mL of concentrated nitric acid and 1 g of conductive carbon black are stirred for 30 min, ultrasonicated for 30 min, condensed and refluxed at 80 ° C for 6 h, and then washed with deionized water for 3 times. After vacuum drying, the acidified carbon-based carrier is obtained;
[0063] S2: Synthesis of Pt precursor dispersion: 200 mg of the acidified carbon-based support was mixed with 5.00 g of potassium chloroplatinate, 14.55 g of Co(NO 3 ) 2 6H 2 O was mixed with deionized water to prepare a 100 mL solution, 100 mL of ethylene glycol was added, and then NaOH solution was added dropwise to adjust the pH to alkaline, and finally ultrasonic treatment was performed for 1 h, and the molar ratio of Pt salt to the second component Co metal salt was 1:5;
[0064] S3: Glow discharge plasma treatment of the synthesized Pt precursor dispersion was performed at 400 V for 30 min;
[0065] S4: The obtained discharge product was washed with methanol for three times and filtered, and the obtained sample was placed in a 60° C. vacuum drying oven for drying, and finally taken out and ground into powder, i.e., Pt-Co-C alloy catalyst.
[0066] Example 4
[0067] Preparation of Pt-Co-Fe-C Alloy Catalyst
[0068] S1: The carbon-based carrier is subjected to an acidification reflux treatment. 100 mL of concentrated nitric acid and 1 g of acetylene black are stirred for 30 min, ultrasonicated for 30 min, condensed and refluxed at 70 ° C for 8 h, and then washed with deionized water for 3 times. After vacuum drying, the acidified carbon-based carrier is obtained;
[0069] S2: Synthesis of Pt precursor dispersion: 200 mg of the acidified carbon-based support was mixed with 0.32 g of platinum nitrate, 1.21 g of Fe(NO 3 ) 3 、1.46g Co(NO 3 ) 2 6H 2 O was mixed with deionized water to prepare a 100 mL solution, 100 mL of ethylene glycol was added, and then NaOH solution was added dropwise to adjust the pH to alkaline, and finally ultrasonic treatment was performed for 0.5 h, and the molar ratio of Pt salt to the second component Ni metal salt was 1:10;
[0070] S3: Glow discharge plasma treatment of the synthesized Pt precursor dispersion was performed at 600 V for 30 min;
[0071] S4: The obtained discharge product was washed with ethanol for three times and filtered, and the obtained sample was placed in a 60° C. vacuum drying oven for drying, and finally taken out and ground into powder, i.e., Pt-Co-Fe-C alloy catalyst.
[0072] Comparative Example 1
[0073] Preparation of Pt-Ni-C alloy catalyst (without adding ethylene glycol to Pt precursor dispersion)
[0074] S1: The carbon-based carrier is subjected to an acidification reflux treatment. 100 mL of concentrated nitric acid and 1 g of Ketjen black are stirred for 30 min, ultrasonicated for 30 min, condensed and refluxed at 60 ° C for 6 h, and then washed with deionized water for 3 times. After vacuum drying, the acidified carbon-based carrier is obtained;
[0075] S2: Synthesis of Pt precursor dispersion: 200 mg of the acidified carbon-based support was mixed with 1.95 g of chloroplatinic acid, 1.45 g of Ni(NO 3 ) 2 6H2 O was mixed with deionized water to prepare a 100 mL solution, and then NaOH solution was added dropwise to adjust the pH to alkaline, and finally ultrasonic treatment was performed for 1 h, and the molar ratio of Pt salt to the second component Ni metal salt was 1:1;
[0076] S3: Glow discharge plasma treatment of the synthesized Pt precursor dispersion was performed at 400 V for 30 min;
[0077] S4: The obtained discharge product was washed with deionized water for three times and filtered, and the obtained sample was placed in a 60° C. vacuum drying oven for drying, and finally taken out and ground into powder, i.e., Pt-Ni-C alloy catalyst.
[0078] Comparative Example 2
[0079] Preparation of Pt-C Alloy Catalyst by Ethylene Glycol Heating Reduction Method
[0080] S1: The carbon-based carrier is subjected to an acidification reflux treatment. 100 mL of concentrated nitric acid and 1 g of Ketjen black are stirred for 30 min, ultrasonicated for 30 min, condensed and refluxed at 60 ° C for 6 h, and then washed with deionized water for 3 times. After vacuum drying, the acidified carbon-based carrier is obtained;
[0081] S2: Synthesis of Pt precursor dispersion: 200 mg of the acidified carbon-based support was mixed with 7.8 g of chloroplatinic acid and added to deionized water to prepare a 100 mL solution, 100 ml of ethylene glycol was added, and then NaOH solution was added dropwise to adjust the pH to alkaline, and finally ultrasonic treatment was performed for 1 h;
[0082] S3: Transfer the above Pt precursor dispersion to a hydrothermal reactor, heat it at 140°C for 2h, and after the hydrothermal reactor is naturally cooled to room temperature, transfer the reaction solution to a beaker;
[0083] S4: The obtained reducing solution was washed with deionized water for three times and filtered, and the obtained sample was placed in a 60° C. vacuum drying oven for drying, and finally taken out and ground into powder, i.e., the Pt-C alloy catalyst.
[0084] Comparative Example 3
[0085] Preparation of Pt-C alloy catalyst by glow discharge method (without adding ethylene glycol to Pt precursor dispersion)
[0086] Preparation of Pt-C alloy catalyst according to the reaction conditions of Example 3 in Patent CN10112175A
[0087] In summary, the main technical parameters of the Pt catalysts prepared in various embodiments and comparative examples are shown in Table 1:
[0088] Table 1 Main technical parameters of Pt catalysts prepared in various examples and comparative examples
[0089]
[0090] Test results and analysis
[0091] (1) Analysis of catalyst morphology and electrochemical performance
[0092] High-resolution transmission electron microscopy (TEM) images ( Figure 1 ) carefully observed that the Pt-Ni-C alloy catalyst prepared in Example 1 significantly showed the characteristics of uniform distribution of Pt nanoparticles on the surface of the carbon-based carrier, no agglomeration of nanoparticles occurred, and the average particle size of the nanoparticles was precisely controlled within the range of about 2.24nm. This microstructural feature is crucial for increasing the specific surface area of the catalyst and improving the density of active sites, and provides strong support for its structural basis of high Pt mass specific activity and high specific surface activity, indicating that the catalyst will show excellent catalytic performance.
[0093] Furthermore, the linear sweep voltammetry (LSV) test ( Figure 2 ) The results show that the half-wave potential of the Pt-Ni-C alloy catalyst after ethylene glycol reduction and glow discharge plasma treatment is significantly better than that of the commercial Pt / C catalyst, indicating better electrocatalytic performance. Similarly, Figure 3 The LSV curve of the Pt-Co-Ni-C alloy catalyst shown also clearly shows that the half-wave potential of the catalyst is significantly improved compared with the commercial Pt / C catalyst, and has better electrocatalytic performance.
[0094] (2) Analysis of catalytic performance results
[0095] The performance and technical parameters of the Pt catalysts prepared in various embodiments and comparative examples are shown in Table 2:
[0096] As can be seen from Table 2, compared with Comparative Example 1 in which ethylene glycol was not used, Comparative Example 2 in which only ethylene glycol thermal reduction was used, and Comparative Example 3 in which the single metal Pt alloy catalyst was not prepared by the ethylene glycol glow discharge method, Examples 1 to 4 of the present invention optimized the preparation conditions and prepared the multi-metal Pt alloy catalyst by combining plasma glow discharge with ethylene glycol reduction, and assisted by condensation reflux pickling to treat the residue, thereby achieving significant improvements in many aspects such as actual Pt loading, Pt mass specific activity, specific surface activity, average particle size and half-wave potential.
[0097] Table 2 Performance and technical parameters of Pt catalysts prepared in various embodiments and comparative examples
[0098]
[0099] Specifically, compared with Comparative Examples 1 and 3, the actual Pt loading of the catalysts prepared in Examples 1 to 4 was increased by about 20% and 10%, respectively. This increase is due to the dual role of ethylene glycol: it acts as a reducing agent to reduce the Pt ions in the Pt salt solution to metallic Pt, and acts as a dispersing solvent to effectively prevent the agglomeration of Pt nanoparticles, ensuring their uniform dispersion on the surface of the carbon-based carrier, thereby improving the loading efficiency and catalytic performance of Pt. In addition, Example 1 further enhances the performance of the carrier through condensation reflux acidification treatment of the carbon-based carrier, promoting the stable loading of Pt nanoparticles.
[0100] Compared with Comparative Example 2 without plasma glow discharge, the actual Pt loading of Examples 1 to 4 increased by about 12%, especially the amount of Pt used in the Pt precursor dispersion during the preparation of Example 4 was only 1% of that of Comparative Example 2; and the average particle size of the Pt nanoparticles was significantly reduced (to a minimum of 2.10 nm, a decrease of 37%). This result shows that compared with high-temperature heat treatment, glow discharge treatment can increase defects on the carrier surface, expand the specific surface area, provide more anchoring sites for Pt nanoparticles, enhance the electronic coupling effect, and promote the uniform distribution of ionomers, significantly improving the catalytic activity.
[0101] In addition, the multi-metal alloy strategy introduces transition metal elements. In Example 4, the ratio of Pt salt to transition metal (second component metal) salt is as low as 1:10, which is equivalent to the 1:1 ratio in Example 1 in terms of increasing Pt loading and ensuring catalyst performance. This strategy not only greatly reduces the amount of precious metal Pt used and controls costs, but also enhances the catalytic activity and anti-poisoning ability of the catalyst.
[0102] In summary, the present invention adds ethylene glycol to the precursor dispersion, effectively solving the technical problem of low Pt loading in the glow discharge catalyst preparation, and achieves an increase in the loading rate of more than 10% while reducing the amount of Pt used; the introduction of transition metal elements greatly reduces the amount of precious metal Pt used at a usage ratio of 1:10, effectively controls the cost, and significantly improves the catalytic activity and anti-poisoning performance of the catalyst.
[0103] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a low-Pt alloy catalyst, characterized in that: The following steps are involved: S1: pretreatment of the carbon-based carrier, adding the carbon-based carrier to an acid solution, dispersing the carbon-based carrier by ultrasonication, and then condensing and refluxing the carbon-based carrier, and washing, filtering, and drying the condensed and refluxed solution to obtain an activated carrier; S2: Preparation of Pt precursor dispersion, dissolving Pt precursor, metal ion salt solution and the activated carrier in water to obtain a mixed solution, adding ethylene glycol to the mixed solution and adjusting the pH of the solution to alkaline, and finally performing ultrasonic treatment to obtain a Pt precursor dispersion; S3: glow discharge plasma treatment, placing the Pt precursor dispersion in a reaction liquid container of a plasma generator, then turning on a DC power switch, adjusting the DC power voltage to perform glow discharge plasma treatment, and obtaining a discharge product; S4: Formation of a Pt alloy catalyst. The discharge product is filtered and washed with a washing liquid, and then dried and ground to obtain a low-Pt alloy catalyst.
2. The method for preparing a low-Pt alloy catalyst according to claim 1, characterized in that: The carbon-based carrier is one of conductive carbon black, carbon nanotubes, graphene, Ketjen black, acetylene black, ethanol, glucose and sucrose.
3. The method for preparing a low-Pt alloy catalyst according to claim 1, characterized in that: The acid solution is one of citric acid, acetic acid, sulfuric acid, perchloric acid, nitric acid, and oxalic acid aqueous solutions, and the concentration of the acid solution is 0.1-2.0 mol / L.
4. The method for preparing a low-Pt alloy catalyst according to claim 1, characterized in that: The temperature of the condensation reflux in step S1 is 60° C. to 80° C., and the duration is 5 to 8 hours. The washing method is to wash with deionized water for 3 to 6 times.
5. The method for preparing a low-Pt alloy catalyst according to claim 1, characterized in that: The Pt precursor includes at least one of chloroplatinic acid, potassium chloroplatinate, potassium chloroplatinite, sodium hexachloroplatinate hexahydrate, sodium chloroplatinite, and platinum nitrate.
6. The method for preparing a low-Pt alloy catalyst according to claim 1, characterized in that: The metal ion salt solution is a salt solution of one or more metal ions selected from non-platinum noble metals and transition metals.
7. The method for preparing a low-Pt alloy catalyst according to claim 1, characterized in that: The volume ratio of the mixed liquid to the ethylene glycol is 1:1-3, the Pt concentration in the Pt precursor dispersion is 0.005-0.05 mol / L, and the molar ratio of Pt to the metal element is 1:1-10.
8. The method for preparing a low-Pt alloy catalyst according to claim 1, characterized in that: The ultrasonic treatment time in step S2 is 30 to 60 minutes.
9. The method for preparing a low-Pt alloy catalyst according to claim 1, characterized in that: The DC power supply voltage of the glow discharge plasma treatment is 400-600V.
10. The method for preparing a low-Pt alloy catalyst according to claim 1, characterized in that: The washing liquid is at least one of deionized water, ethanol and methanol.
Citation Information
Patent Citations
Supported catalyst as well as preparation method and application thereof
CN108855166A
Platinum-carbon catalyst prepared by atmospheric pressure discharge technology as well as preparation method and application of platinum-carbon catalyst
CN117039031A
Heat exchange system for exchanging heat with a formable material
KR1020240131895A
Cluster-supporting porous carrier and method for producing same
US20210077986A1
KR20240071508A